2017
DOI: 10.2967/jnumed.117.194654
|View full text |Cite
|
Sign up to set email alerts
|

Improved Estrogen Receptor Assessment by PET Using the Novel Radiotracer 18F-4FMFES in Estrogen Receptor–Positive Breast Cancer Patients: An Ongoing Phase II Clinical Trial

Abstract: After encouraging preclinical and human dosimetry results for the novel estrogen receptor (ER) PET radiotracer 4-fluoro-11β-methoxy-16α-F-fluoroestradiol (F-4FMFES), a phase II clinical trial was initiated to compare the PET imaging diagnostic potential of F-4FMFES with that of 16α-F-fluoroestradiol (F-FES) in ER-positive (ER+) breast cancer patients. Patients diagnosed with ER+ breast cancer ( = 31) were recruited for this study, including 6 who underwent mastectomy or axillary node dissection. For each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Moreover, the hepatic uptake and biliary excretion of this tracer additionally complicate the detection of lesions in this region. FES also shows affinity to plasma globulins which results in a reduced amount of tracer available for targeting the ER receptors expressing cells [ 19 ]. A modification of the estradiol to 4-fluoro-11β-methoxy-16α-[ 18 F]FES ([ 18 F]4FMFES) lowers tracer affinity for plasmatic globulins, accelerates blood clearance, and decreases uptake in nonspecific organs compared to [ 18 F]FES [ 19 , 64 ].…”
Section: Direct Targeting Of Tumor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the hepatic uptake and biliary excretion of this tracer additionally complicate the detection of lesions in this region. FES also shows affinity to plasma globulins which results in a reduced amount of tracer available for targeting the ER receptors expressing cells [ 19 ]. A modification of the estradiol to 4-fluoro-11β-methoxy-16α-[ 18 F]FES ([ 18 F]4FMFES) lowers tracer affinity for plasmatic globulins, accelerates blood clearance, and decreases uptake in nonspecific organs compared to [ 18 F]FES [ 19 , 64 ].…”
Section: Direct Targeting Of Tumor Cellsmentioning
confidence: 99%
“…In a Phase II clinical trial, the diagnostic potential of [ 18 F]4FMFES was further evaluated. The tracer showed a similar tumor targeting potential to [ 18 F]FES but had superior imaging properties due to decreased overall background allowing higher detection rates and better sensitivity towards ER + BCa [ 19 ].…”
Section: Direct Targeting Of Tumor Cellsmentioning
confidence: 99%
“…Additional phase II data regarding the diagnostic accuracy of 18 F-fluoroestradiol imaging have been published by Paquette et al (13). The performance of a newer ER-targeted radiopharmaceutical, 4-fluoro-11b-methoxy-16a-18 F-fluoroestradiol, or 18 F-4FMfluoroestradiol, was compared with 18 F-fluoroestradiol in 31 patients with ER-positive breast cancer.…”
Section: Assessment Of Er Statusmentioning
confidence: 99%
“…Sun Y in 2015 investigated the contribution of FES PET/CT in determining ER positive metastatic lesions from breast cancer, suggesting that 18 F-FES PET/CT by assessing the entire tumor volume receptor Kruchten et al, 2013;Dehdashti et al, 1995;Linden et al, 2006;Peterson et al, 2008;Peterson et al, 2011;Mintun et al, 1988;Sun et al, 2015) 4 status, it may be used to assist the individualized treatment decisions of breast cancer patients (Sun et al, 2015). Paquette et al (2017) took ER imaging a step forward by their phase II clinical trial, which was conducted to compare the PET imaging diagnostic potential of 4-fluoro-11β-methoxy-16α-[ 18 F] fluoroestradiol (4FMFES) to FES in ER positive breast cancer patients. They found that 4FMFES-PET achieves lower non-specific signal and better tumor contrast than FES-PET, promising improved diagnostic confidence and lower false negative diagnoses (Paquette et al, 2017).…”
Section: Targeting Of Hormone Receptorsmentioning
confidence: 99%
“…Paquette et al (2017) took ER imaging a step forward by their phase II clinical trial, which was conducted to compare the PET imaging diagnostic potential of 4-fluoro-11β-methoxy-16α-[ 18 F] fluoroestradiol (4FMFES) to FES in ER positive breast cancer patients. They found that 4FMFES-PET achieves lower non-specific signal and better tumor contrast than FES-PET, promising improved diagnostic confidence and lower false negative diagnoses (Paquette et al, 2017).…”
Section: Targeting Of Hormone Receptorsmentioning
confidence: 99%